Chemical Composition and Antibacterial Screening of Aerial Parts of Essential Oils of Three Satureja species (Satureja briquetti, Satureja atlantica and Satureja alpina) Growing Wild in the Middle Atlas Mountains of Morocco. Issue 3 (4th May 2018) - Jennan, Sanae; Fouad, Rida; Nordine, Aicha; Farah, Abdellah; Bennani, Bahia; Moja, Sandrine; Greche, Hassane; Mahjoubi, Fatima
Abstract: Hydro-distilled essential oils from the aerial parts of Satureja briquetti, S. atlantica and S. alpina, which are growing wild in the middle Atlas Mountains of Morocco, were analyzed by GC-MS. Different compounds were identified in the three plant oils, representing 96.25%, 98.19% and 98.18% of the total oil respectively. The major constituents of essential oil obtained from the plant material of S. briquetti, were borneol (27.64%), β-bisabolène (9.58%), α-pinene (6.97%) and linalool (6.77%).The most abundant compounds in essential oil of S. atlantica were piperitenone oxide (24.27%), limonene (20.57%), pulegone (16.88%) and cis -piperitone oxide (15.55%). Pulegone (87.74%) was identified as the main component in the essential oil of S. alpina . The screening of antibacterial activity of essential oil samples was individually evaluated against twelve bacteria species using a disc diffusion method. In addition, the Minimal inhibitory concentration (MIC) was determined. The results showed that the essential oil of S. alpina has stronger and broader spectrum of antibacterial activity as compared to S. briquetti and S. atlantica .